Gender-based differences in language learning strategies among undergraduates in a Malaysian public university - Ho, Ai Ping; Ng, Lee Luan (UNIMAS Publisher, 2016)
Unemployment among the Malaysian public universities’ graduates due to their inability to communicate proficiently and accurately in English language with proper pronunciation has been a concern among various parties. One possible method to address such issue is to look at how these graduates learn and improve their command of English language. Language learning strategies (LLS) is one of the prominent variables that can affect their language learning process. With that in view, this study investigated the LLSs used by the first year undergraduates in a Malaysian public university. It also examined the relationship between language learning strategies based on gender. The survey utilised the Strategy Inventory for Language Learning (SILL) by Oxford (1990) on 535 male and 1173 female respondents. Data obtained were analysed using descriptive statistics, t-test, One-way ANOVA and chi-square test. Finding revealed that females employed more strategies if compared to males. The research result also showed that metacognitive strategies were highly employed by these undergraduates whereas affective strategies were least used among them. Further ANOVA test revealed there was a significant difference between the language learning strategies used by these undergraduates. The implications of these findings to educators, scholars and researchers were also discussed.